A cross-layer protocol for cooperative content delivery over mobile ad-hoc networks. (1st January 2011) - Greco, Claudio; Cagnazzo, Marco
Real-time multimedia streaming over MANETs is an active research field since this technology promises scalable and robust audio/video delivery without infrastructure. Even though this problem has several commune features with peer-to-peer routing, the additional sensible parameters of MANETs make wired solutions unfit to this case; therefore, we propose a content routing/delivery protocol inherently designed for the ad-hoc wireless case, exploiting the intrinsic broadcast property of the medium. We provided an implementation of this protocol and we tested it in several use-cases, observing how it assures availability, robustness and scalability.